An Expanded Polyproline Domain Maintains Mutant Huntingtin Soluble in vivo and During Aging - Pigazzini, Maria Lucia; Lawrenz, Mandy; Margineanu, Anca; Kaminski Schierle, Gabriele S.; Kirstein, Janine (Frontiers in Molecular Neuroscience, 2021)
Huntington´s disease is a dominantly inherited neurodegenerative disorder caused by the expansion of a CAG repeat, encoding for the amino acid glutamine (Q), present in the first exon of the protein huntingtin (HTT). Over the threshold of Q39 HTT exon 1 (HTTEx1) tends to misfold and aggregate into large intracellular structures, but whether these end-stage aggregates or their on-pathway intermediates are responsible for cytotoxicity is still debated. HTTEx1 can be separated into three domains: an N-terminal 17 amino acid (N17) region, the polyglutamine (polyQ) expansion and a C-terminal proline rich domain (PRD). Alongside the expanded polyQ, these flanking domains influence the aggregation propensity of HTTEx1: with the N17 initiating and promoting aggregation, and the PRD modulating it. In this study we focus on the P1, comprising the first 11 amino acids of the PRD, a stretch of pure prolines, which are an evolutionary recent addition to the expanding polyQ region. We hypothesize that this proline region is expanding alongside the polyQ to counteract its ability to misfold and cause toxicity, and that expanding this proline region would be overall beneficial. We generated HTTEx1 mutants lacking both flanking domains singularly, missing the first 11 prolines of the PRD, or with this stretch of prolines expanded. We then followed their aggregation landscape in vitro with a battery of biochemical assays, and in vivo in novel models of C. elegans expressing the HTTEx1 mutants pan-neuronally. Employing fluorescence lifetime imaging we could observe the aggregation propensity of all HTTEx1 mutants during aging and correlate this with toxicity via various phenotypic assays. We found that the presence of an expanded proline stretch is beneficial in maintaining HTTEx1 soluble over time, regardless of polyQ length. However, the expanded prolines were only advantageous in promoting the survival and fitness of an organism carrying a pathogenic stretch of Q48 but were extremely deleterious to the nematode expressing a physiological stretch of Q23Q. Our results reveal the unique importance of the prolines which have and still are evolving alongside expanding glutamines to promote the function of HTTEx1 and avoid pathology.